Reinterpreting the role of traditional Chinese medicine in public health in rural China in 1970s - Fang, Xiaoping (Orient Blackswan, 2021)
From their first appearance, the barefoot doctors attracted the attention of scholars and social commentators. The barefoot doctor program has been regarded, both inside and outside of China, as “a low-cost solution built around easily available indigenous medicines.” They presented a suitably revolutionary image: young people who waded undaunted through the mud of the rice paddies to provide medical services in answer to Mao’s call to “stress rural areas in medical and health work.” Their main equipment was popularly described as “one silver needle and a bunch of herbs”, a reference to acupuncture and Chinese herbal medicine, but they combined Chinese and Western medicine in medical practice. Together with the three-tiered rural medical system, barefoot doctors and cooperative medical services have been associated with improvements in basic health indicators under socialism after the founding of the People’s Republic of China in 1949. In the late 1970s, the WHO promoted the Chinese system as a model of primary health care for developing countries.